2009
DOI: 10.1111/j.1756-185x.2009.01375.x
|View full text |Cite
|
Sign up to set email alerts
|

Status of oxidative stress in rheumatoid arthritis

Abstract: Aim: To assess the oxidative stress status in rheumatoid arthritis by measuring markers of free radical production, systemic activity of disease, free radical mediated tissue destruction and levels of antioxidant. Methods:Peripheral blood samples were used for all the assays. Total nitric oxide (NO) was quantitatively measured using immunoassay kit. Malondialdehyde (MDA) and vitamin E were measured by spectrophotometric methods.Results: Statistically significant changes were observed in the levels of MDA, vita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(72 citation statements)
references
References 31 publications
5
64
0
3
Order By: Relevance
“…production by articular chondrocytes and synovial fibroblasts and elevated levels of NO . are observed in the serum and synovial fluid of RA patients [190]. The free radicals, particularly NO and O 2…”
Section: Cataractmentioning
confidence: 98%
“…production by articular chondrocytes and synovial fibroblasts and elevated levels of NO . are observed in the serum and synovial fluid of RA patients [190]. The free radicals, particularly NO and O 2…”
Section: Cataractmentioning
confidence: 98%
“…Additionally, we also observed the significantly higher levels of saturated and mono-unsaturated PC but lower levels of polyunsaturated PC and polyunsaturated PE in the RA group compared with the healthy group. Studies have demonstrated the presence of oxidative stress in RA [23][24][25] and the excess reactive oxygen species (ROS) production could disturb the redox status, damage macromolecules and exacerbate inflammation. 26,27 The primary targets of ROS are double bonds in polyunsaturated fatty acids in the membrane phospholipids, 27,28 which make the cell membrane change in fluidity and permeability, and finally lead to the changes in cell structure and function.…”
Section: Discussionmentioning
confidence: 99%
“…The symptoms of RA, such as joint swelling, pain, stiffness, and other complications, may hamper the physical training and reduce physical fitness [30,31]. Chronic inflammation and destruction of the joints result in deformities that also exacerbate the inactivity in the patients with RA [27]. This makes a vicious cycle in which the inactivity resulted in decreased muscular balance and joint deformity that in turn causes pain and disability.…”
Section: Discussionmentioning
confidence: 99%